The quiet threat : fighting industrial espionage in America - Mendell, Ronald L. (Charles C Thomas, 2003)
"Industrial espionage is a craft that has evolved over the centuries that remains persistent in its threat. History has shown us that the techniques used today are adaptations of those developed in the sixteenth century and honed through the twentieth century. Accordingly, the text focuses on the similarity of industrial spy craft through time with examples from Anglo-American history. This book will help security professionals to combat industrial (or corporate) espionage in the post-industrial information age by helping to understand its techniques. A primary goal of the book is in giving the reader a real sense of how industrial spies are persistent and clever in circumventing defenses."--BOOK JACKET.